(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Coronavirus disease 2019 (COVID-19) has swept across the globe overwhelming health care systems and disrupting supply chain of personal protective equipment (PPE) like gloves, surgical face masks, goggles, face shields, N95 respirators and gowns. Surging demand, panic buying, hoarding, and misuse of PPE has led to substantial jump in its demand. Despite the terrible impact of COVID-19, if there’s any silver lining to this crisis, it is the rapidity at which communities are moving toward innovation in not just medicine and remote work but also in ways to mitigate the growing PPE shortages.